Edukasi Bahaya Penyalahgunaan Antibiotik dan Pemaanfaatan Tanaman Herbal untuk Pengobatan - Endah Prayekti; Nathalya Dwi Kartika Sari; Ary Andini; Renny Novi Puspitasari; Yauwan Tobing Lukiyono; Khiliah Navis (Warmadewa University Press, 2023)
Antibiotics are generally known in the community as a medicine for disease. The use of antibiotics in society is often not matched by knowledge of the consequences of misuse of antibiotics. One of the most dangerous effects of uncontrolled use of antibiotics in humans, animals, or animal products is the presence of bacterial resistance to antibiotics. The existence of bacterial resistance to antibiotics causes infected patients to take longer to recover. The purpose of this community service activity is to provide education to Tanjung Gresik Village Health cadres on the correct use of antibiotics and provide insight into the use of herbal plants as natural medicines. The method of implementing community service is carried out using the seminar method and followed by the distribution of booklets and flyers for reading material for village cadres. After implementation, village cadres are required to fill out an understanding evaluation form for the material that has been provided. The results of the initial measurement indicated that 33 village cadres had knowledge regarding antibiotics, but only an average of 13 participants were able to answer the initial questions correctly. Initial measurements related to herbal plants for treatment, of the 15 herbal plants that were informed, 10 herbal plants had known benefits. While the other 5 herbal plants have not been widely known for their benefits for treatment. After the activity, the understanding of cadres has increased. Increased understanding of the use of antibiotics reached 25% for 16 participants, 50% for 3 participants, and 75% for 1 participant. While the use of herbal plants increased by 5-30% for 9 participants, > 20-30% for 5 participants and > 50% for 5 participants. Based on the results obtained from this activity, village cadres can use the information obtained to be conveyed to residents.